1107 Supplementing Orthopaedic Education outside of the Medical Curriculum: The Utility of a 1-Day Orthopaedic Revision Course for Medical Undergraduates. (12th October 2021) - Argyriou, A; Michael, S; Nadeem, K; Batra, G
Abstract: Introduction: Orthopaedic undergraduate education is both minimal and variable across UK medical schools. Furthermore, the clinical skills required to treat musculoskeletal injuries have been found inadequate by several studies assessing UK medical graduates. Method: Orthopaedic revision courses organized by the student surgical society consisted of lectures and workshops covering clinical orthopaedic knowledge and skills required for university assessments. Five identical courses were run between December 2017 and December 2019 following the completion of fourth year's musculoskeletal clinical block. Course tutors ranged from foundation year doctors (57%) to orthopaedic consultants and trainees (43%). An anonymous feedback form was handed out at each event and 5-point Likert scale questioning assessed participant perceptions prior to and following the course. Results: This course led to a significant mean increase in students' perceived knowledge levels with an average increase of 0.96 (19.2%) across all clinical examinations and lectures (p < 0.01). Tutor grade did not affect mean participant self-reported value of station, with stations taught by consultants and surgical trainees showing similar results to stations taught by FY doctors (p = 0.776). Conclusions: The feedback revealed significant increases in student self-reported knowledge levels while poor pre-course scores reported might suggest inadequate coverage of orthopaedics in the undergraduate curriculum. The similarity in results when assessing the quality of tutorship suggests that FY doctors can be equally as valuable teaching tools for such courses as surgical trainees and consultants. These results suggest 1-day orthopaedic revision courses of this format can be highly beneficial in supplementing the undergraduate curriculum.